A stochastic model for secured online transaction using Monty Hall problem. (2021) - Maruthi Shankar, B.; Sivakumar, S.A.; Vidhya, B.; Saranya, G.; Naveen Kumar, D.; Kiruthik Prakash, J.
Abstract: The abstract Probability is somewhat difficult for those who can't imagine and hard to understand. This is due to the unsolved probability applications. Here let us discuss one of the unsolved applications of probability. It is Monty Hall. It is a game played between Alice and Bob but it's not true it's the game played between Alice and the host. The gameplay of Monty hall is that the player chooses one of the three doors and the host opens any of the other two doors and it always opens the door which makes the player lose and it again asks the player whether he remains with the same door or else change the door If the work of host is implemented in the field of encoding process so that there will be no permanent encoded code for a particular transaction it always changes for every online transaction so that the rate of online crime can be decreased. Thus the unsolved Monty hall problem gives a solution and a new way to protect the online transactions.